Effects of discrete heat source location on heat transfer and entropy generation of nanofluid in an open inclined L-shaped cavity. Issue 4 (10th December 2018) - Armaghani, Taher; Rashad, A.M.; Vahidifar, Omid; Mishra, S.R.; Chamkha, A.J.
Abstract : Purpose: This paper aims to concentrate on the impacts of a discrete heat source location on heat transfer and entropy generation for a Ag-water nanofluid in an open inclined L-shaped cavity. Design/methodology/approach: The governing partial differential equations for this study are computed by the finite volume method. Findings: The results show that increasing the inclination angle leads to a rise in heat transfer. It is clear with the increase in the nanoparticles volume fraction that the thermal performance reduces, and it increases when the inclination angle increases. Originality/value: Because of the continuous literature survey, the authors have not found a study that concentrates on the entropy generation in a wide variety of irregular ducts. Thus, in this paper, they present the analysis of entropy generation in an L-shaped duct experiencing a mixed convective flow with a nanofluid. The authors deal with this geometry because it is very useful in cooling systems of nuclear and chemical reactors and electronic components.